Understanding the scale and nature of avoidable healthcare-associated harm for prisoners in England: protocol for a retrospective cross-sectional study - Andrew Carson-Stevens; Maria Panagioti; Adrian Edwards; Jenny Shaw; Stephen Campbell; Carl de Wet; Kate Davies; Anthony Avery; Stuart Hellard; Melanie Jordan; Caroline Sanders; Isobel Joy McFadzean; et al. (BMJ Open)
Introduction Around 1 in 20 patients experience avoidable healthcare-associated harm worldwide. Despite longstanding concerns, there is insufficient information available about the safety of healthcare for prisoners. To address this, this study will investigate the scale and nature of avoidable healthcare-associated harm for prisoners in England.Methods We will undertake a large retrospective cross-sectional study involving a case note review of patient healthcare records in 18 prisons in England. Prisons will be purposively sampled for maximum variation of characteristics based on prison category (open, local, training, high security, female), type (publicly and privately run) and prison population size, to sample approximately 15 000 patient records. We will focus on two samples: an enhanced risk sample of prisoners, considered to be at the most risk of healthcare-associated harm, and a random sample of prisoners excluded from the enhanced risk sample, to estimate the incidence of avoidable harm, and express this as ‘per 100 000 patients per year’. Avoidable harms will be characterised by type of incident(s), contributory incident(s), contributory factor(s), outcome(s) and severity of harm, prior to a thematic analysis of the relationships between those variables. Univariable and multivariable analyses will be conducted to identify factors associated with avoidable harm.Ethics and dissemination The decision regarding participation by prisons within the study will be voluntary, and their consent to participate may be withdrawn at any time. We will not seek individual patient consent for the retrospective case note review of their records, but if patients respond to publicity about the project and inform us that they do not wish their records to be included, we will adhere to their wishes. We will produce a report for the Department of Health’s Policy Research Programme and several peer-reviewed publications. The study has been granted a favourable opinion by Wales Research Ethics Committee 3 (reference 19/WA/0291), Her Majesty’s Prison and Probation Service (reference 2019–332) and the Confidentiality Advisory Group (CAG) to access the medical records without individual consent under Section 251 of the National Health Service Act 2006 (reference 19/CAG/0214).